Model Penelitian Pendidikan Agama Islam Berbasis Integrasi-Interkoneksi : Analisis Pendekatan Pohon Ilmu, Jaring Laba-Laba, dan Twin Tower - Munawir Saharuddin; Tobroni Tobroni (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2024)
This study examines the effectiveness of three integration-interconnection models in Islamic Religious Education (PAI): the Tree of Knowledge Model, the Spider Web Model, and the Twin Towers Model. These models are designed to bridge religious knowledge and general sciences, enriching a holistic approach in Islamic education. The Tree of Knowledge Model positions religious values as the ethical foundation for all disciplines, integrating faith as the basis for understanding general knowledge. The Spider Web Model envisions education as an interconnected, interdisciplinary network, enhancing students' ability to perceive connections across various fields. The Twin Towers Model balances the roles of religious and general sciences, promoting moderation and openness among students. The study findings suggest that these models help reduce the dichotomy between religious and secular sciences and assist students in developing a comprehensive and relevant understanding of both disciplines. The study recommends adopting these models into the PAI curriculum, providing comprehensive teacher training, and developing integrated learning modules to prepare Islamic education students to face contemporary social and scientific challenges with critical thinking and a strong ethical foundation.